2020
DOI: 10.3389/fneur.2020.596454
|View full text |Cite
|
Sign up to set email alerts
|

Ocular vs. Cervical Vestibular Evoked Myogenic Potentials in Benign Paroxysmal Positional Vertigo: A Systematic Review and Meta-Analysis

Abstract: Objective: To compare utricular dysfunction with saccular dysfunction in benign paroxysmal positional vertigo (BPPV), based on ocular vestibular evoked myogenic potentials (oVEMP) and cervical VEMP (cVEMP), respectively. Materials and Methods: We performed a literature search exploring utricular and saccular dysfunction in BPPV patients through June 2020 using oVEMP and cVEMP, respectively. The databases included Pubmed, Embase, CENTRAL, CNKI, Wan Fang Data, and CBM. The literatures were limited to Chinese and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Makowiec et al [16] reported that patients with vestibular migraine may exhibit normal cVEMP responses in the presence of unilaterally abnormal oVEMP responses. The absence of oVEMP more than cVEMP has also been reported in individuals with severe to profound sensorineural hearing loss [17], patients with bilateral vestibulopathy due to aminoglycosides toxicity [18], and BPPV [19]. Thus, the absence of oVEMP more than cVEMP may not be a significant biomarker for the diagnosis of vestibular pathology in patients with vestibular migraine.…”
Section: Response Ratementioning
confidence: 99%
“…Makowiec et al [16] reported that patients with vestibular migraine may exhibit normal cVEMP responses in the presence of unilaterally abnormal oVEMP responses. The absence of oVEMP more than cVEMP has also been reported in individuals with severe to profound sensorineural hearing loss [17], patients with bilateral vestibulopathy due to aminoglycosides toxicity [18], and BPPV [19]. Thus, the absence of oVEMP more than cVEMP may not be a significant biomarker for the diagnosis of vestibular pathology in patients with vestibular migraine.…”
Section: Response Ratementioning
confidence: 99%
“…Benign paroxysmal positional vertigo is unlikely to cause persistent symptoms of imbalance as it is not associated with unilateral vestibular weakness during videonystagmogram testing, although some studies have described persistent VEMP abnormalities in patients with a history of BPPV. 42 Our study excluded patients with a diagnosis of Ménière disease or BPPV.…”
Section: Enrollment Criteria In the Literaturementioning
confidence: 99%
“…[ 4 – 6 ] Of it, benign paroxysmal positional vertigo (BPPV) accounts for most common type of vertigo. [ 7 10 ] It occurs in the inner ear because of the changes in position. [ 9 12 ] Although standard treatment is applied to manage such disorder, its 1-year recurrence rate is about 20%, and its 4 to 5 year recurrence rate is between 40% and 50%.…”
Section: Introductonmentioning
confidence: 99%